Preliminary studies of alfaxalone for intravenous immobilization of juvenile captive estuarine crocodiles (Crocodylus porosus) and Australian freshwater crocodiles (Crocodylus johnstoni) at optimal and selected sub‐optimal thermal zones. (6th March 2013) - Olsson, Annabelle; Phalen, David; Dart, Christina
Abstract: Objectives: To investigate the character of immobilization given by alfaxalone in juvenile crocodiles at optimal and at suboptimal temperatures. Study design: Prospective, randomized partial crossover study. Animals: Twenty captive male estuarine (weight 0.6–2.5 kg) and five captive male freshwater crocodiles (weight 0.2–0.6 kg). Methods: Crocodiles were acclimatized for 24 hours at one of the following environmental temperatures; 32 °C, 27 °C, 22 °C or 17 °C, then received 3 mg kg −1 intravenous (IV) alfaxalone into the dorsal occipital venous sinus. Duration and quality of immobilization was assessed and heart rate (HR) measured. On a separate occasion each crocodile was immobilized at one other environmental temperature. Results: Alfaxalone, 3 mg kg −1 IV, produced immobilization for 55 (range 15–100 minutes in estuarine, and 20 (range 20–25) minutes in freshwater crocodiles at 32 °C. There was no significant difference overall in immobilization times between temperatures, other than that, in estuarine crocodiles, duration was shorter at 32 °C than 22 °C. The character of immobilization was unpredictable, with animals recovering without warning, or having extended recoveries requiring assisted ventilation. Assisted ventilation was necessary mainly at the lower temperatures. Median HR in all temperature treatments decreased within 5 minutes post‐injection, but the change in HR over the duration of immobilization was affected by the temperature, with a progressively smaller range of fall as temperature decreased. At 17 °C, two estuarine crocodiles appeared to re‐immobilize after initial recovery, became severely bradycardiac and required ventilation and re‐warming. Conclusions and clinical relevance: Alfaxalone IV in small captive estuarine and freshwater crocodiles provides adequate induction of immobilization at various temperatures. However, the unpredictable results following induction mean it is unsuitable for field use and should be restricted to environments where intubation and ventilation are available, where animals can be warmed to optimal temperature, and where access to immersion in water can be restricted for 24 hours.